An Examination of the Experiences of Black Football Athletes - Jeff Porter (University of Kansas Libraries, 2019)
The purpose of this study was to understand the experiences of Black college athletes that played football and graduated from a Division I Power 5 institution. It is well documented that Black football players graduate from Power 5 institutions lower rates than any other student or athlete group, due to a variety of obstacles they face on campus. Despite these obstacles, there are athletes in this group who do graduate from their institution and successfully transition into professional careers. The research conducted for this article is adapted from a dissertation that explores the campus environment that Black college football players must navigate. This article focuses on the impact the social support network has, helping these athletes maneuver through their organizational environment and prepare for life after athletics. Understanding the possible influences of a support network can be a critical strategy for the survival of this group of athletes.